Biologia reprodutiva e estrutura populacional de Prochilodus lineatus em um remanescente lótico da Bacia do Rio Grande - Violeta da Rocha Perini (2013)
The Grande River is known for its high capacity of power generation, and in its channel several large plants were established, fragmenting its course, changing the ecosystem and reducing native biodiversity. The present study evaluated the reproductive biology and population genetics of Prochilodus lineatus in the system composed by Grande River, Pardo River and Mogi Guaçu River, between Porto Colombia dam and Cachoeira de Emas. Specimens were collected bimonthly at the following sampling sites: (S1) located in the Grande River, immediately downstream from the Porto Colômbia dam, (S1') in the Grande River, immediately downstream from the confluence with the Pardo River; (S2) in the Pardo River, 110 km from S1, (S3) in the Mogi Guaçu River, region of Cachoeira de Emas, about 200 km from S2, and (S4) in the Pardo River, upstream from the confluence with the Mogi Guaçu River, about 40 km from S2. To evaluate the reproductive biology, the following parameters were analyzed: gonadosomatic index (GSI), gonadal maturation stages, vitellogenic follicle diameter (OD), follicular atresia (FA), fecundity (AF) and plasmatic levels of sex steroids. In S1, maturing fish showed changes in reproductive parameters: lower values of GSI, OD, FA and AF, compared to S2 and S3. The frequency of maturing fish was higher in sites S2 and S3, and spawning was recorded only in S3. Absolute fecundity ranged from 27.55 x 10³ to 440.47 x 10³, being greater at site S2. In sites S2 and S3, seric concentrations of testosterone and 17-estradiol in females and testosterone in males showed large variations during gonadal maturation, while fish from S1 showed minor variations. The 17-hydroxyprogesterone levels remained high in mature fish in sites S2 and S3, where females reached the final oocyte maturation. The results indicated that P. lineatus does not reproduce the Grande River (S1), but probably uses the Pardo River (S2) as migratory route towards the Mogi Guaçu River (S3), where it completes its gonadal maturation and spawning. For analysis of population structure, samples of adipose fin of 30 specimens of P. lineatus were collected at sites S1, S1', S2, S3 and S4 during the breeding season. Samples were subjected to DNA extraction, PCR amplification and microsatellite analysis using 10 primers described for the genus Prochilodus. All microsatellites used were polymorphic, with numbers of alleles per locus ranging from 5 to 32. From the 179 alleles detected, 32 were private for their sample site and were at low frequency ( 0.05), and the two most frequente private alleles were detected in site S4. Fish from site S1 presented higher inbreeding coefficient, which presented correlation with abiotic characteristics of the sites studied. The data indicate that P. lineatus does not constitute a panmitic genetic population in the study area, but it is divided into three clusters which coexist and maintain a low level of structuring, which could not be related to geographic isolation, but to homing behavior. Furthermore, P. lineatus populations could constitute a metapopulation influenced by a source-sink dynamics, in which the sites located in tributaries (S2, S3 and S4) would act as sources of individuals and the sites located in the main River (S1 and S1') as a sink area. To assess hepatic histopathology, liver fragments of P. lineatus were collected in the three rivers of the study and the following parameters were analyzed: occurrence of apoptosis, hepatosomatic index (HSI), and index of tecidual injury (IL). The IL was calculated considering the occurrence and the importance of six alterations: necrosis, nuclear changes, inflammatory infiltration, vacuolation, hyperemia and cytoplasmic granulation. Significant differences related to the sample site of the specimens were observed, with fish from S1 presenting higher IL and occurrence of necrosis than fish from sites S2 and S3. The HSI and the occurrence of apoptosis showed no significant differences between the sampling sites. Together, the results of this study contribute to the understanding of the behavior and biology of P. lineatus in its natural environment, as well as provide important parameters for the conservation and management of their populations and fish farming.